Five Finger Techniques with Gayatri Mantra to Reduce Anxiety of Family with Schizophrenia - Desakmadearidwijayanti; Arwidiana, Dewa Putu; Mirayanti, Ni Ketut Ayu (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Anxiety is a condition felt when a person faces a stressor. The five-finger technique focuses on the five fingers to get a relaxed state, and the Gayatri Mantra is a prayer in Hinduism that can give you peace. This study aims to determine the five-finger technique with Gayatri Mantra to reduce anxiety in families of people with schizophrenia. Objective: The study aimed to examine the effect of the Five Fingers Technique with Gayatri Mantra on Anxiety Levels among Families of People with Schizophrenia. Methods: The research design used a pre-experiment, One-group, Pre-test, and Post-test. A total of 22 people were selected using the purposive sampling technique. The anxiety level is measured by using the HRS-A   questionnaire. The study was conducted six times in a row for 15 minutes. Results: The results showed the pre-test score for mild anxiety was 45.5%, moderate anxiety was 54.5%, and post-test was not anxious at 31.8%, mild anxiety was 40.9%, and moderate anxiety was 27.3%. The results of the bivariant test with Wilcoxon obtained a p-value of 0.004 (p <0.05). Conclusion: The conclusion is that the five finger technique with the Gayatri Mantra can reduce the anxiety of families of people with schizophrenia at the Sukawati II Public Health Center, Gianyar. Recommendation: It is recommended that families apply the five-finger technique with the Gayatri Mantra in their daily life